KONSEP MA’RIFAT DALAM TASAWUF ATAS PEMIKIRAN IMAM AL GHAZALI - Azis, Taufik Burhanudin (AT-TAJDID, 2024)
he term Sufism is no longer foreign to Muslim scholars, both in Indonesia and in othercountries. Sufism is known as Islamic mysticism or Sufism. Sufism is also popular as ascience of direct knowledge of God and its teachings and methods come from the Koranand Al Hadith, the inspiration of pious people, as well as the kasyf (openness of the heart)of wise people. Sufism has indeed become a scientific study that is greatly admired byscholars. Because moral messages start from the relationship between humans and otherhumans, to the relationship between humans and God. In the initial study of Sufism, aperson will usually be introduced to the term a person's level of worship or devotion toAllah SWT. namely shar'iat, tarekat, essence and makrifat. Sufis usually distinguishbetween the meanings of these levels. Therefore, this article explains the concept ofCopyright © 2024, Universitas Muhammadiyah Metro| 348ma'riat in Sufism based on the thoughts of Imam al-Ghazali. The concept of ma'rifat inal-Ghazali's Sufism offers the concept of suluk or path by: Searching for knowledge,Tafakkur, and Tazkiyat an-nafs. Meanwhile, to achieve ma'rifat according to al-Ghazali,there are stages in the form of: Isolating oneself (al-uzlah), remaining silent (as-samt),being hungry (al-ju), and being awake or not sleeping at night (as -sahar). Meanwhile,ma'rifat according to al-Ghazali's view is knowing Allah SWT, knowing God's form whichincludes all forms, there is no existence apart from Allah SWT.